2010
DOI: 10.1111/j.2041-1626.2010.00023.x
|View full text |Cite
|
Sign up to set email alerts
|

Australian opinions on water fluoridation: do Queenslanders believe differently?

Abstract: Perceived Queensland characteristics, which political scientists have used to explain aberrant political behavior or public policy, were not relevant to the longstanding pre-2009 disparity in water fluoridation coverage between Queensland and the rest of Australia. The findings of this investigation do not support the assumption that Queenslanders are more opposed to fluoridation than residents elsewhere in Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…A concentration of research into the attitudes of Australians to CWF has occurred in recent years, 9,11,12,14 presumably because of the widespread coverage of CWF in most states and recent activity extending coverage in Queensland. Recent studies in Australia report higher levels of support for CWF than in this study, and have found that the majority of people support CWF.…”
Section: Oral Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…A concentration of research into the attitudes of Australians to CWF has occurred in recent years, 9,11,12,14 presumably because of the widespread coverage of CWF in most states and recent activity extending coverage in Queensland. Recent studies in Australia report higher levels of support for CWF than in this study, and have found that the majority of people support CWF.…”
Section: Oral Healthmentioning
confidence: 99%
“…5,6 Opinion is influenced by a range of factors, including evidence-based information from health authorities and organisations, personal beliefs and heath promotion programs, 5,6 and is also strongly influenced by anti-fluoridation information. 7 While it has recently been reported that more than 90% of NZ dentists support CWF, 8 and overseas reports of public opinion about CWF are available, [9][10][11][12][13][14] there are few scientific reports of the opinions of the NZ public regarding CWF. A 2001 telephone survey of Onehunga residents reported that, while 55% of NZ European respondents were in favour of CWF, only 33% of Māori and Pacific respondents and 38% of Asian respondents were in favour.…”
mentioning
confidence: 99%
“…Studies have identified socio-economic status as an independent factor in determining support, with those of lower socio-economic status more likely to oppose water fluoridation. 9,10,12 As well, both a lack of trust in authority and a desire for greater community autonomy have statistically significant predictive values for opposition to water fluoridation. 11,12 Previous data have been derived mainly from studies using quantitative methodologies, limiting the breadth of potential responses and restricting effective exploration of the reasons for opposition.…”
Section: Introductionmentioning
confidence: 99%
“…9,10,12 As well, both a lack of trust in authority and a desire for greater community autonomy have statistically significant predictive values for opposition to water fluoridation. 11,12 Previous data have been derived mainly from studies using quantitative methodologies, limiting the breadth of potential responses and restricting effective exploration of the reasons for opposition. The Royal Society of New Zealand published a review of the scientific evidence on the health effects of water fluoridation and reported that:…”
Section: Introductionmentioning
confidence: 99%
“…The addition of fluoride into the public water system has been highly debated among both the general public and the Queensland Government for many decades. Several surveys conducted in Queensland between 1997 and 2007 show the support for water fluoridation to vary from 60% to 73.4% . Despite claims of public concerns and hesitation to support water fluoridation, an analysis of 405 newspaper portrayals of fluoridation in Queensland from December 2007–July 2010 concluded that fluoridation appeared to generate minimal electoral repercussions…”
Section: Introductionmentioning
confidence: 99%